2021
DOI: 10.3389/fcell.2021.723346
|View full text |Cite
|
Sign up to set email alerts
|

TR35 Exerts Anti-tumor Effects by Modulating Mitogen-Activated Protein Kinase and STAT3 Signaling in Lung Cancer Cells

Abstract: Cancer is a complex disease extremely dependent on its microenvironment and is highly regulated by a variety of stimuli inside and outside the cell. Evidence suggests that active camel whey fraction (TR35) confer anti-tumor effects in non-small cell lung cancer (NSCLC). However, its exact mechanisms remain elusive. Here, we investigated the mechanisms underlying suppression of NSCLC cell growth and proliferation by TR35. Treatment of A549 and H1299 cells with TR35 suppressed their growth and enhanced apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Nanobodies were reported in camels in the early 1980s, the presence of which makes camels unique. Importantly, camel milk contains nanobodies that potentially can be used as a promising tool for diagnosing and targeting metastatic cancers [36][37][38][39].…”
Section: Arabian Camel's Genome and Nanobodies Emergencementioning
confidence: 99%
See 1 more Smart Citation
“…Nanobodies were reported in camels in the early 1980s, the presence of which makes camels unique. Importantly, camel milk contains nanobodies that potentially can be used as a promising tool for diagnosing and targeting metastatic cancers [36][37][38][39].…”
Section: Arabian Camel's Genome and Nanobodies Emergencementioning
confidence: 99%
“…Furthermore, the active camel whey fraction (TR35) was found to display anti-tumorigenic effects in non-small lung cancer. This was accomplished through promoting in vitro cancer cells apoptosis and inhibiting tumour growth in vivo model via activation of JNK phosphorylation and suppression of P38 and STAT3 phosphorylation [39]. The tumours battling power provided by the camel milk were validated by numerous in vitro and in vivo investigations [59][60][61][62][63].…”
Section: Involvement Of Camels' Biological Secretions In Remedying Di...mentioning
confidence: 99%
“…Accordingly, camel milk has high application value, especially as a substitute for hypoallergenic infant formula (Maryniak et al 2018). Furthermore, it exhibits anti-inflammation (Al-Omari et al 2019;Patel et al 2021), anti-hypertension, antidiabetes (Mudgil et al 2018) and anti-cancer activities (El-Kattawy et al 2021;Shi et al 2021) as well as having important medical value in the treatment of liver and kidney injury (Usman et al 2020;Dou et al 2022). Milk composition is an important indicator reflecting the quality of dairy products and the health status of dairy animals.…”
Section: Introductionmentioning
confidence: 99%
“…p38 MAPK and STAT3 signalling are activated in most of cancer cells and participate in cancer cell proliferation and metastases 21,22 . Suppression of p38 MAPK and STAT3 activation was associated with reduced lung cancer growth in vitro and in animal models 23,24 . However, the role and downstream signalling pathways of SIRPα in the progression of lung cancer are not well studied so far.…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 Suppression of p38 MAPK and STAT3 activation was associated with reduced lung cancer growth in vitro and in animal models. 23 , 24 However, the role and downstream signalling pathways of SIRPα in the progression of lung cancer are not well studied so far. We in this study, for the first time, investigated the role of SIRPα in SIRPα knock‐out (KO) mice and found that lack of SIRPα significantly reduced lung cancer cell growth in mice, in association with improved MPs and neutrophils (NPs) phagocytosis and reduced IL‐6 expression in tumour tissues.…”
Section: Introductionmentioning
confidence: 99%